The influence of second order narrow-band colored noises on non-linear random vibrations - Anh, Nguyen Dong; Tinh, Nguyen Duc (Vietnam Journal of Mechanics, 1999)
Since the effect of some nonlinear terms is lost during the first order averaging procedure, the higher order stochastic averaging method is developed to predict approximately the response of linear and lightly nonlinear systems subject to weakly external excitation of second order colored noise random processes. Application to Duffing oscillator is considered.